A method for manufacturing a weather-resistant crystalline silicon solar cell

The transparent coating liquid with a crosslinking network structure is prepared by combining fluorocarbon resin with methacrylic resin, and combined with a light stabilizer and cetyl trimethylamine bromide to prepare sol to form a weather-resistant transparent back plate, which solves the aging and yellowing problems caused by the inability to reflect ultraviolet rays of existing transparent back plates, and significantly improves the ultraviolet resistance and service life of solar cells.

CN119364870BActive Publication Date: 2025-05-16NINGBO OSDA SOLAR CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411911727.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-05-16
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Because the existing transparent back panel cannot reflect ultraviolet rays, it is prone to material aging and yellowing due to long-term exposure to ultraviolet environments, which affects the service life of solar cells and environmental weather resistance.

Method used

By combining fluorocarbon resin with methacrylic resin, a transparent coating liquid with a crosslinking network structure was prepared, and the surface of the PET layer was coated, and the sol was prepared in combination with a light stabilizer and cetyl trimethylamine bromide to form a weather-resistant transparent back plate.

Benefits of technology

It improves the UV resistance of the transparent backplane, slows down the aging process of solar cells, extends its service life, and improves the weather resistance of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119364870B_ABST
    Figure CN119364870B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of photovoltaic equipment, and in particular to a method for manufacturing a weather-resistant crystalline silicon solar cell. The preparation method comprises the following steps: weathering treatment of a main resin; preparing a transparent coating liquid; preparing a transparent backplane; preparing a high-transmittance stability film; coating a light-stable high-transmittance film; and assembling a solar cell. The present invention improves the weather resistance of a fluorocarbon resin by compounding a fluorocarbon resin with a methacrylic resin. The methacrylic resin molecule contains a double bond, which can form a cross-linked network structure through free radical polymerization, and the fluorocarbon resin can form an interpenetrating network structure with the methacrylic resin molecule. This cross-linked network structure can improve the density and stability of the coating, reduce ultraviolet rays from penetrating the interior of the coating, and the transparent coating liquid prepared by compounding the fluorocarbon resin with the methacrylic resin is coated on the surface of the PET layer to prepare a transparent backplane, thereby playing an anti-ultraviolet effect, slowing down the aging process of the solar cell, and improving the weather resistance of the solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic equipment, and in particular to a method for manufacturing a weather-resistant crystalline silicon solar cell. Background Art

[0002] Crystalline silicon solar panels usually include a backplane, a panel, and a solar cell unit between the two, wherein the backplane is located at the outermost layer on the back of the battery module, and plays a supporting and protective role for the battery module. Since solar cells are usually used in outdoor environments, the backplane, as the outermost layer on the back of the solar cell module, is often in direct contact with the external environment, and needs to protect the core components of the solar cell from various factors such as water vapor and ultraviolet rays. By improving the performance of solar cell packaging materials such as the backplane, crystalline silicon solar cells can have good environmental weather resistance.

[0003] In the prior art, the backplane of solar cells is often made of transparent materials, which enables the solar cells to absorb more light, thereby improving the utilization rate of solar energy in the environment by the solar cells. Since the transparent backplane cannot reflect ultraviolet rays, it is easy for the material to age and turn yellow due to long-term exposure to ultraviolet rays. The degradation of the backplane performance will directly affect the service life and environmental weather resistance of the solar cell. Therefore, the present invention provides a method for manufacturing weather-resistant crystalline silicon solar cells to solve the problems existing in the above-mentioned prior art. Summary of the invention

[0004] In view of the shortcomings of the prior art, an object of the present invention is to provide a method for manufacturing a weather-resistant crystalline silicon solar cell.

[0005] A method for manufacturing a weather-resistant crystalline silicon solar cell comprises the following steps:

[0006] S1: Weathering treatment of main resin

[0007] Take a fluorocarbon resin, add N, N-dimethylacetamide, stir evenly to prepare a dispersion with a fluorocarbon resin concentration of 50wt%, then add methacrylic resin and mix and stir, then add glycidyl methacrylate and dibasic acid ester DBE, stir, stir evenly, add dispersant, epoxy resin defoamer and leveling agent in sequence to obtain a weather-resistant main resin;

[0008] S2: Preparation of transparent coating liquid

[0009] Weather-resistant main resin, anti-hydrolysis agent, nano-SiO 2 , dispersant and ethyl acetate are added into a beaker, dispersed, allowed to stand for defoaming, and then curing agent and diluent are added, stirred evenly to obtain a transparent coating solution;

[0010] S3: Preparation of transparent backplane

[0011] On the insulating layer PET, an adhesive is applied, and then a layer of transparent coating liquid is applied using a wire rod, and the surface is dried at 150-160°C and dried at 60-65°C for 24-26 hours to obtain a transparent backplane;

[0012] S4: Preparation of high permeability and stability membrane

[0013] S4.1: In a four-mouth reactor equipped with a thermometer, acetone, 4-vinyl benzoate and 2,2,6,6-tetramethyl-4-hydroxypiperidine are added, a condenser is installed, and a stirrer is started. The temperature is raised to reflux and water is separated. After the water separation is completed, 0.8-1.2 parts by weight of tetrabutyl titanate catalyst is added. When the reaction temperature is controlled to 120-125°C, the reaction time is controlled to 8-10h. After the reaction is completed, the reaction is washed with water, and the organic phase is collected. The organic phase is dehydrated, decolorized, and crystallized to obtain a light stabilizer;

[0014] S4.2: Add tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid, hexadecyltrimethylammonium bromide and light stabilizer to the reactor in sequence, stir for 15-20 minutes, reflux the sol at 70-80°C for 5-6 hours, age for 24-26 hours, and filter the prepared sol with a 0.22um polyvinylidene fluoride membrane to obtain a sol for membrane preparation;

[0015] S5: Coated with light-stable high-transmittance film

[0016] The film-forming sol is coated on the surface of the transparent back sheet, and dried at 60° C. for 12 hours to obtain a weather-resistant transparent back sheet;

[0017] S6: Assembling solar cells

[0018] Arrange the crystalline silicon cells, place the arranged cell strings on the EVA film, cover with a glass panel and a weather-resistant transparent backplane, and then put into a laminator to cure under high temperature and high pressure to obtain a solar cell module. Install an aluminum frame on the edge of the laminated cell module, install a junction box and connect the external circuit to obtain a weather-resistant crystalline silicon solar cell.

[0019] Furthermore, step S1 of weathering the main resin comprises the following steps:

[0020] S1.1: Take 30 parts by weight of fluorocarbon resin, add N,N-dimethylacetamide, stir evenly to prepare a dispersion with a fluorocarbon resin concentration of 50wt%, then add methacrylic acid resin and mix and stir at a speed of 200-300r / min for 5-10min;

[0021] S1.2: Then add 3 parts by mass of glycidyl methacrylate and 30 parts by mass of dibasic acid ester DBE, and stir at a speed of 800-850 r / min for 3-3.5 hours;

[0022] S1.3: After stirring evenly, 2 parts by weight of dispersant, 1 part by weight of epoxy resin defoamer and 1.5 parts by weight of leveling agent are added in sequence to obtain a weather-resistant main resin.

[0023] Furthermore, step S2 of preparing a transparent coating liquid comprises the following steps:

[0024] S2.1: 100 parts by weight of weather-resistant main resin, 1.2 parts by weight of anti-hydrolysis agent, 2-3.9 parts by weight of nano-SiO 2 , 0.3 parts by mass of dispersant and 150 parts by mass of ethyl acetate are added into a beaker in a certain amount, dispersed at a speed of 1000-1200 r / min for 1-1.5 hours, and allowed to stand for defoaming for 20-25 minutes;

[0025] S2.2: Then add 8.6-12.6 parts by mass of curing agent and 121-150 parts by mass of diluent, stir evenly, and obtain a transparent coating liquid.

[0026] Furthermore, step S6 assembling the solar cell comprises the following steps:

[0027] S6.1: Arrange the crystalline silicon cells and connect the positive and negative electrodes of the cells using solder strips or conductive paste to form cell strings and battery packs;

[0028] S6.2: placing the arranged battery strings on the EVA film, covering with a glass panel and a weather-resistant transparent back sheet, and then placing in a laminator, curing under high temperature and high pressure to obtain a solar cell module;

[0029] S6.3: Install an aluminum frame on the edge of the laminated battery assembly, install a junction box and connect the external circuit to obtain a weather-resistant crystalline silicon solar cell.

[0030] Furthermore, the mass ratio of the fluorocarbon resin to the methacrylic resin is (9-5):4.

[0031] Furthermore, the anti-hydrolysis agent is a silane coupling agent, and the dispersant is a polysilicate dispersant.

[0032] Furthermore, the curing agent is an epoxy resin curing agent, and the diluent is acetone.

[0033] Furthermore, the mass ratio of acetone, 4-vinyl benzoate and 2,2,6,6-tetramethyl-4-hydroxypiperidine is 10:1:3.

[0034] Furthermore, the mass ratio of tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid, hexadecyltrimethylammonium bromide and light stabilizer is 1:12:23:0.2:0.1:5.

[0035] Compared with the prior art, the present invention has at least the following beneficial effects:

[0036] 1. The present invention improves the weather resistance of fluorocarbon resin by compounding fluorocarbon resin with methacrylic resin. Methacrylic resin molecules contain double bonds and can form a cross-linked network structure through free radical polymerization. Fluorocarbon resin carries vinyl groups. Free radicals such as vinyl groups can polymerize with double bonds, so that methacrylic resin molecules form an interpenetrating network structure. This cross-linked network structure can improve the density and stability of the coating and reduce ultraviolet rays from penetrating the interior of the coating. A transparent coating liquid prepared by compounding fluorocarbon resin and methacrylic resin is coated on the surface of a PET layer to prepare a transparent backplane, thereby playing an anti-ultraviolet effect, slowing down the aging process of solar cells, and improving the weather resistance of solar cells.

[0037] 2. The present invention prepares a light stabilizer by using acetone, 4-vinyl benzoate and 2,2,6,6-tetramethyl-4-hydroxypiperidine. The benzene ring contained in the structure of 4-vinyl benzoate can effectively absorb ultraviolet rays, especially in the UV-B region (290-320nm), showing a good absorption effect, which helps to reduce the damage of ultraviolet rays to the transparent backplane. The carboxylate group of 4-vinyl benzoate imparts a certain polarity, which helps to obtain better dispersibility and compatibility in the system, so that after mixing with acetone, it is better compatible with 2,2,6,6-tetramethyl-4-hydroxypiperidine, that is, the stability accommodates more 2,2,6,6-tetramethyl-4-hydroxypiperidine molecules, and the hydroxyl groups of the 2,2,6,6-tetramethyl-4-hydroxypiperidine molecules capture the escape of free radicals of the transparent backplane material caused by ultraviolet rays, and the escaped free radicals are subjected to hydrogen transfer oxidation-reduction, so that the escaped free radicals of the transparent backplane material are captured and restored to the original state, thereby playing a light stabilizing role.

[0038] 3. The present invention prepares a sol by compounding a light stabilizer with hexadecyltrimethylammonium bromide and coating the sol on a transparent backplane, thereby improving the anti-ultraviolet ability of solar cells while ensuring the light transmittance of the weather-resistant transparent backplane. Hexadecyltrimethylammonium bromide, as a cationic surfactant, can effectively reduce the aggregation of nanoparticles in a solvent, and the addition of the light stabilizer can further optimize the interaction between particles, improve the dispersion stability and morphology control of nanomaterials, and while the light stabilizer provides ultraviolet protection, the hydrophobic group of hexadecyltrimethylammonium bromide can help the light stabilizer form an ultraviolet protection layer. The two work together to improve the weather resistance of the solar cell.

[0039] 4. The present invention prepares a weather-resistant main resin by adding glycidyl methacrylate to a fluorocarbon resin. The epoxy group in glycidyl methacrylate has excellent polarity and reactivity, and can form strong chemical bonds with a variety of substrates. Additional cross-linking points are formed through the ring-opening reaction of the epoxy group, thereby increasing the density of the resin network and improving the hardness and wear resistance of the transparent coating film prepared from the weather-resistant main resin. The transparent backplane prepared from the transparent coating has better hardness and is not easily worn or damaged, thereby significantly improving the weather resistance of the solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.

[0041] Figure 1 This is a flow chart of a method for manufacturing a weather-resistant crystalline silicon solar cell adopted in an embodiment of the present invention. DETAILED DESCRIPTION

[0042] The following is a detailed description of a method for manufacturing a weather-resistant crystalline silicon solar cell provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0043] Embodiment 1:

[0044] A method for manufacturing a weather-resistant crystalline silicon solar cell, such as Figure 1 As shown, the following steps are included:

[0045] S1: Weathering treatment of main resin

[0046] S1.1: Take 30 parts by weight of fluorocarbon resin, add N,N-dimethylacetamide, stir evenly to prepare a dispersion with a fluorocarbon resin concentration of 50wt%, then add methacrylic resin and mix and stir, the mass ratio of fluorocarbon resin to methacrylic resin is 9:4, the rotation speed is 200r / min, and the stirring time is 5min;

[0047] S1.2: Then add 3 parts by mass of glycidyl methacrylate and 30 parts by mass of dibasic acid ester DBE, and stir at a speed of 800 r / min for 3 h;

[0048] S1.3: After stirring evenly, add 2 parts by mass of a polysilicate dispersant, 1 part by mass of an epoxy resin defoamer and 1.5 parts by mass of a FEVE fluorocarbon resin modified leveling agent in sequence to obtain a weather-resistant main resin.

[0049] S2: Preparation of transparent coating liquid

[0050] S2.1: 100 parts by weight of weather-resistant main resin, 1.2 parts by weight of silane coupling agent, 2 parts by weight of nano-SiO 2 , 0.3 parts by mass of polysilicate dispersant and 150 parts by mass of ethyl acetate were added into a beaker in a certain amount, dispersed at a speed of 1000 r / min for 1 hour, and allowed to stand for defoaming for 20 minutes;

[0051] S2.2: Then add 8.6 parts by mass of epoxy resin curing agent and 121 parts by mass of acetone, stir evenly, and obtain a transparent coating liquid.

[0052] S3: Preparation of transparent backplane

[0053] Adhesive was applied on the insulating layer PET, and then a layer of transparent coating liquid was applied using a wire rod. The surface was dried at 150° C. and dried at 60° C. for 24 hours to obtain a transparent backplane.

[0054] S4: Preparation of high permeability and stability membrane

[0055] S4.1: In a four-mouth reactor equipped with a thermometer, acetone, 4-vinyl benzoate and 2,2,6,6-tetramethyl-4-hydroxypiperidine are added, the mass ratio of acetone, 4-vinyl benzoate and 2,2,6,6-tetramethyl-4-hydroxypiperidine is 10:1:3, a condenser is installed, the stirrer is started, the temperature is raised and refluxed to separate water, after the separation of water is completed, 0.8 parts by mass of tetrabutyl titanate catalyst is added, the reaction temperature is controlled at 120°C, the reaction time is controlled at 8h, after the reaction is completed, the reaction is washed with water, the organic phase is collected, and the organic phase is dehydrated, decolorized and crystallized to obtain a light stabilizer;

[0056] S4.2: Add tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid, hexadecyl trimethyl ammonium bromide and light stabilizer to the reactor in sequence, the mass ratio of tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid, hexadecyl trimethyl ammonium bromide and light stabilizer is 1:12:23:0.2:0.1:5, stir for 15 minutes, and reflux the sol at 70°C for 5 hours after stirring. After aging for 24 hours, filter the prepared sol with a 0.22um polyvinylidene fluoride membrane to obtain a sol for membrane preparation.

[0057] S5: Coated with light-stable high-transmittance film

[0058] The film-forming sol was coated on the surface of the transparent backplane and dried at 60° C. for 12 hours to obtain a weather-resistant transparent backplane.

[0059] S6: Assembling solar cells

[0060] S6.1: Arrange the crystalline silicon cells and connect the positive and negative electrodes of the cells using solder strips or conductive paste to form cell strings and battery packs;

[0061] S6.2: placing the arranged battery strings on the EVA film, covering with a glass panel and a weather-resistant transparent back sheet, and then placing in a laminator, curing under high temperature and high pressure to obtain a solar cell module;

[0062] S6.3: Install an aluminum frame on the edge of the laminated battery assembly, install a junction box and connect the external circuit to obtain a weather-resistant crystalline silicon solar cell.

[0063] Embodiment 2:

[0064] A method for manufacturing a weather-resistant crystalline silicon solar cell, such as Figure 1 As shown, the following steps are included:

[0065] S1.1: Take 30 parts by weight of fluorocarbon resin, add N,N-dimethylacetamide, stir evenly to prepare a dispersion with a fluorocarbon resin concentration of 50wt%, then add methacrylic resin and mix and stir, the mass ratio of fluorocarbon resin to methacrylic resin is 5:4, the rotation speed is 200r / min, and the stirring time is 5min;

[0066] S1.2: Then add 3 parts by mass of glycidyl methacrylate and 30 parts by mass of dibasic acid ester DBE, and stir at a speed of 800 r / min for 3 h;

[0067] S1.3: After stirring evenly, add 2 parts by mass of a polysilicate dispersant, 1 part by mass of an epoxy resin defoamer and 1.5 parts by mass of a FEVE fluorocarbon resin modified leveling agent in sequence to obtain a weather-resistant main resin.

[0068] S2: Preparation of transparent coating liquid

[0069] S2.1: 100 parts by weight of weather-resistant main resin, 1.2 parts by weight of silane coupling agent, 3.9 parts by weight of nano-SiO 2 , 0.3 parts by mass of polysilicate dispersant and 150 parts by mass of ethyl acetate were added into a beaker in a certain amount, dispersed at a speed of 1000 r / min for 1 hour, and allowed to stand for defoaming for 20 minutes;

[0070] S2.2: Then add 12.6 parts by mass of epoxy resin curing agent and 150 parts by mass of acetone, stir evenly, and obtain a transparent coating liquid.

[0071] S3: Preparation of transparent backplane

[0072] Adhesive was applied on the insulating layer PET, and then a layer of transparent coating liquid was applied using a wire rod. The surface was dried at 150° C. and dried at 60° C. for 24 hours to obtain a transparent backplane.

[0073] S4: Preparation of high permeability and stability membrane

[0074] S4.1: In a four-mouth reactor equipped with a thermometer, acetone, 4-vinyl benzoate and 2,2,6,6-tetramethyl-4-hydroxypiperidine are added, the mass ratio of acetone, 4-vinyl benzoate and 2,2,6,6-tetramethyl-4-hydroxypiperidine is 10:1:3, a condenser is installed, the stirrer is started, the temperature is raised to reflux and water is separated, after the water separation is completed, 1.2 parts by mass of catalyst tetrabutyl titanate is added, the reaction temperature is controlled at 120°C, the reaction time is controlled at 8h, after the reaction is completed, the reaction is washed with water, the organic phase is collected, and the organic phase is dehydrated, decolorized and crystallized to obtain a light stabilizer;

[0075] S4.2: Add tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid, hexadecyl trimethyl ammonium bromide and light stabilizer to the reactor in sequence, the mass ratio of tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid, hexadecyl trimethyl ammonium bromide and light stabilizer is 1:12:23:0.2:0.1:5, stir for 15 minutes, and reflux the sol at 70°C for 5 hours after stirring. After aging for 24 hours, filter the prepared sol with a 0.22um polyvinylidene fluoride membrane to obtain a sol for membrane preparation.

[0076] S5: Coated with light-stable high-transmittance film

[0077] The film-forming sol was coated on the surface of the transparent backplane and dried at 60° C. for 12 hours to obtain a weather-resistant transparent backplane.

[0078] S6: Assembling solar cells

[0079] S6.1: Arrange the crystalline silicon cells and connect the positive and negative electrodes of the cells using solder strips or conductive paste to form cell strings and battery packs;

[0080] S6.2: placing the arranged battery strings on the EVA film, covering with a glass panel and a weather-resistant transparent back sheet, and then placing in a laminator, curing under high temperature and high pressure to obtain a solar cell module;

[0081] S6.3: Install an aluminum frame on the edge of the laminated battery assembly, install a junction box and connect the external circuit to obtain a weather-resistant crystalline silicon solar cell.

[0082] Embodiment 3:

[0083] A method for manufacturing a weather-resistant crystalline silicon solar cell, such as Figure 1 As shown, the following steps are included:

[0084] S1.1: Take 30 parts by weight of fluorocarbon resin, add N,N-dimethylacetamide, stir evenly to prepare a dispersion with a fluorocarbon resin concentration of 50wt%, then add methacrylic resin and mix and stir, the mass ratio of fluorocarbon resin to methacrylic resin is 9:4, the rotation speed is 300r / min, and the stirring time is 10min;

[0085] S1.2: Then add 3 parts by mass of glycidyl methacrylate and 30 parts by mass of dibasic acid ester DBE, and stir at a speed of 850 r / min for 3 hours;

[0086] S1.3: After stirring evenly, add 2 parts by mass of a polysilicate dispersant, 1 part by mass of an epoxy resin defoamer and 1.5 parts by mass of a FEVE fluorocarbon resin modified leveling agent in sequence to obtain a weather-resistant main resin.

[0087] S2: Preparation of transparent coating liquid

[0088] S2.1: 100 parts by weight of weather-resistant main resin, 1.2 parts by weight of silane coupling agent, 2 parts by weight of nano-SiO 2 , 0.3 parts by mass of polysilicate dispersant and 150 parts by mass of ethyl acetate were added into a beaker in a certain amount, dispersed at a speed of 1200 r / min for 1.5 hours, and allowed to stand for defoaming for 25 minutes;

[0089] S2.2: Then add 8.6 parts by mass of epoxy resin curing agent and 121 parts by mass of acetone, stir evenly, and obtain a transparent coating liquid.

[0090] S3: Preparation of transparent backplane

[0091] Adhesive was applied on the insulating layer PET, and then a layer of transparent coating liquid was applied using a wire rod. The surface was dried at 160° C. and dried at 65° C. for 26 hours to obtain a transparent backplane.

[0092] S4: Preparation of high permeability and stability membrane

[0093] S4.1: In a four-mouth reactor equipped with a thermometer, acetone, 4-vinyl benzoate and 2,2,6,6-tetramethyl-4-hydroxypiperidine are added, the mass ratio of acetone, 4-vinyl benzoate and 2,2,6,6-tetramethyl-4-hydroxypiperidine is 10:1:3, a condenser is installed, the stirrer is started, the temperature is raised and refluxed to separate the water, after the separation of water is completed, 0.8 parts by mass of tetrabutyl titanate catalyst is added, the reaction temperature is controlled at 125°C, the reaction time is controlled at 10h, after the reaction is completed, the reaction is washed with water, the organic phase is collected, and the organic phase is dehydrated, decolorized and crystallized to obtain a light stabilizer;

[0094] S4.2: Add tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid, hexadecyl trimethyl ammonium bromide and light stabilizer to the reactor in sequence, the mass ratio of tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid, hexadecyl trimethyl ammonium bromide and light stabilizer is 1:12:23:0.2:0.1:5, stir for 20 minutes, and reflux the sol at 80°C for 6 hours after stirring. After aging for 26 hours, filter the prepared sol with a 0.22um polyvinylidene fluoride membrane to obtain a sol for membrane preparation.

[0095] S5: Coated with light-stable high-transmittance film

[0096] The film-forming sol was coated on the surface of the transparent backplane and dried at 60° C. for 12 hours to obtain a weather-resistant transparent backplane.

[0097] S6: Assembling solar cells

[0098] S6.1: Arrange the crystalline silicon cells and connect the positive and negative electrodes of the cells using solder strips or conductive paste to form cell strings and battery packs;

[0099] S6.2: placing the arranged battery strings on the EVA film, covering with a glass panel and a weather-resistant transparent back sheet, and then placing in a laminator, curing under high temperature and high pressure to obtain a solar cell module;

[0100] S6.3: Install an aluminum frame on the edge of the laminated battery assembly, install a junction box and connect the external circuit to obtain a weather-resistant crystalline silicon solar cell.

[0101] Comparative Example 1:

[0102] Compared with Example 1, the difference of Comparative Example 1 is that no methacrylic resin is added in step S1, specifically: "S1.1: Take 30 parts by mass of fluorocarbon resin, add N,N-dimethylacetamide, stir evenly to prepare a dispersion with a fluorocarbon resin concentration of 50wt%, then add methacrylic resin and mix and stir, the mass ratio of fluorocarbon resin to methacrylic resin is 9:4, the rotation speed is 200r / min, and the stirring time is 5min;

[0103] S1.2: Then add 3 parts by mass of glycidyl methacrylate and 30 parts by mass of dibasic acid ester DBE, and stir at a speed of 800 r / min for 3 h;

[0104] S1.3: After stirring evenly, 2 parts by mass of a polysilicate dispersant, 1 part by mass of an epoxy resin defoamer and 1.5 parts by mass of a FEVE fluorocarbon resin modified leveling agent were added in sequence to obtain a weather-resistant main resin. The weather-resistant transparent backsheet prepared in step S5 is recorded as Comparative Example 1.

[0105] Comparative Example 2:

[0106] Compared with Example 1, the difference of Comparative Example 2 is that no light stabilizer is added in step S4, specifically: "S4: Preparation of high light stability film

[0107] S4.2: Add tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid and hexadecyl trimethyl ammonium bromide into the reactor in sequence, the mass ratio of tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid and hexadecyl trimethyl ammonium bromide is 1:17:23:0.2:0.1, stir for 15 minutes, and reflux the sol at 70°C for 5 hours after stirring. After aging for 24 hours, filter the prepared sol with a 0.22um polyvinylidene fluoride membrane to obtain a "sol for membrane preparation", and record the weather-resistant transparent backboard prepared in step S5 as comparative example 2.

[0108] Comparative Example 3:

[0109] Compared with Example 1, the difference of Comparative Example 3 is that hexadecyltrimethylammonium bromide is not added in step S4, specifically: "S4: Preparation of high permeability stability membrane

[0110] S4.1: In a four-mouth reactor equipped with a thermometer, acetone, 4-vinyl benzoate and 2,2,6,6-tetramethyl-4-hydroxypiperidine are added, the mass ratio of acetone, 4-vinyl benzoate and 2,2,6,6-tetramethyl-4-hydroxypiperidine is 10:1:3, a condenser is installed, the stirrer is started, the temperature is raised and refluxed to separate water, after the separation of water is completed, 0.8 parts by mass of tetrabutyl titanate catalyst is added, the reaction temperature is controlled at 120°C, the reaction time is controlled at 8h, after the reaction is completed, the reaction is washed with water, the organic phase is collected, and the organic phase is dehydrated, decolorized and crystallized to obtain a light stabilizer;

[0111] S4.2: Add tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid and light stabilizer to the reactor in sequence, the mass ratio of tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid, hexadecyltrimethylammonium bromide and light stabilizer is 1:12:23:0.2:5.1, stir for 15 minutes, and reflux the sol at 70°C for 5 hours after stirring. After aging for 24 hours, filter the prepared sol with a 0.22um polyvinylidene fluoride membrane to obtain a sol for film making. The weather-resistant transparent backplane prepared in step S5 is recorded as comparative example 3.

[0112] Comparative Example 4:

[0113] Compared with Example 1, the difference of Comparative Example 4 is that glycidyl methacrylate is not added in step S1, specifically: "S1.1: Take 30 parts by mass of fluorocarbon resin, add N,N-dimethylacetamide, stir evenly to prepare a dispersion with a fluorocarbon resin concentration of 50wt%, then add methacrylic resin and mix and stir, the mass ratio of fluorocarbon resin to methacrylic resin is 9:4, the rotation speed is 200r / min, and the stirring time is 5min;

[0114] S1.2: Then, 33 parts by weight of dibasic acid ester DBE was added and stirred at 800 r / min for 3 h;

[0115] S1.3: After stirring evenly, 2 parts by mass of a polysilicate dispersant, 1 part by mass of an epoxy resin defoamer and 1.5 parts by mass of a FEVE fluorocarbon resin modified leveling agent were added in sequence to obtain a weather-resistant main resin. The weather-resistant transparent backsheet prepared in step S5 is recorded as Comparative Example 4.

[0116] Antioxidant activity test

[0117] The weather-resistant transparent backsheets of Examples 1-3 and Comparative Examples 1-4 were placed in an accelerated UV aging device, with the coating surface facing the light source for a cumulative irradiation of 200 kWh / m 2 Then, the yellowing, light transmittance, tensile strength and elongation at break of the test pieces before and after aging were tested in accordance with GB / T31034-2014, and the gloss of the test pieces before and after aging were tested in accordance with GB9754-2007. The results are shown in Tables 1 and 2.

[0118] Table 1: Elongation at break

[0119]

[0120] Table 2: Yellowing value

[0121]

[0122] In the table, the elongations at break of Examples 1-3 are 146%, 144% and 143% respectively, while the elongation at break of Comparative Example 1 is only 125%. The higher the elongation at break, the better the physical strength of the material. The yellowing values ​​of Examples 1-3 are 1.51, 1.47 and 1.49, while that of Comparative Example 1 is 2.96. The lower the yellowing value, the lower the degree of performance aging of the material under ultraviolet irradiation, that is, it is more resistant to ultraviolet irradiation. It can be seen that the cross-linked network structure formed by the composite of methacrylic resin and fluorocarbon resin improves the density and stability of the coating, thereby improving the physical strength of the weather-resistant transparent backplane, and at the same time, such a cross-linked network structure also reduces the penetration of ultraviolet rays into the coating, thereby improving the anti-ultraviolet performance.

[0123] The elongations at break of Comparative Examples 2 and 3 are 136% and 134% respectively, while the yellowing values ​​are 2.24 and 2.73. It can be seen that the composite preparation of the sol by the light stabilizer and hexadecyltrimethylammonium bromide does not improve the physical properties of the material much, but significantly improves the anti-ultraviolet performance. This is because while the light stabilizer provides ultraviolet protection, the hydrophobic group of hexadecyltrimethylammonium bromide can help the light stabilizer to form an ultraviolet protection layer. The combined effect of the two is better than that of a single one.

[0124] The elongation at break of comparative example 4 is 129%, and the yellowing value is 1.79, indicating that glycidyl methacrylate can provide an improvement in hardness for fluorocarbon resin, but the improvement in UV resistance is relatively weak, and the main role of light stabilizers and hexadecyltrimethylammonium bromide in UV resistance is played.

[0125] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for manufacturing a weather-resistant crystalline silicon solar cell, characterized in that: The steps include: S1: Weathering treatment of main resin Take a fluorocarbon resin, add N, N-dimethylacetamide, stir evenly to prepare a dispersion with a fluorocarbon resin concentration of 50wt%, then add methacrylic resin and mix and stir, then add glycidyl methacrylate and dibasic acid ester DBE, stir, stir evenly, add dispersant, epoxy resin defoamer and leveling agent in sequence to obtain a weather-resistant main resin; S2: Preparation of transparent coating liquid Add the weather-resistant main resin, anti-hydrolysis agent, nano-SiO2, dispersant and ethyl acetate into a beaker, disperse, let stand to defoam, then add the curing agent and diluent, stir evenly to obtain a transparent coating solution; S3: Preparation of transparent backplane On the insulating layer PET, an adhesive is applied, and then a layer of transparent coating liquid is applied using a wire rod, and the surface is dried at 150-160°C and dried at 60-65°C for 24-26 hours to obtain a transparent backplane; S4: Preparation of high permeability and stability membrane S4.1: In a four-mouth reactor equipped with a thermometer, acetone, 4-vinyl benzoate and 2,2,6,6-tetramethyl-4-hydroxypiperidine are added, a condenser is installed, and a stirrer is started. The temperature is raised to reflux and water is separated. After the water separation is completed, 0.8-1.2 parts by weight of tetrabutyl titanate catalyst is added. When the reaction temperature is controlled to 120-125°C, the reaction time is controlled to 8-10h. After the reaction is completed, the reaction is washed with water, and the organic phase is collected. The organic phase is dehydrated, decolorized, and crystallized to obtain a light stabilizer; S4.2: Add tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid, hexadecyltrimethylammonium bromide and light stabilizer to the reactor in sequence, stir for 15-20 minutes, reflux the sol at 70-80°C for 5-6 hours, age for 24-26 hours, and filter the prepared sol with a 0.22um polyvinylidene fluoride membrane to obtain a sol for membrane preparation; S5: Coated with light-stable high-transmittance film The film-forming sol is coated on the surface of the transparent back sheet, and dried at 60° C. for 12 hours to obtain a weather-resistant transparent back sheet; S6: Assembling solar cells Arrange the crystalline silicon cells, place the arranged cell strings on the EVA film, cover with a glass panel and a weather-resistant transparent backplane, and then put into a laminator to cure under high temperature and high pressure to obtain a solar cell module. Install an aluminum frame on the edge of the laminated cell module, install a junction box and connect the external circuit to obtain a weather-resistant crystalline silicon solar cell.

2. The method for manufacturing a weather-resistant crystalline silicon solar cell according to claim 1, characterized in that: Step S1: weathering treatment of the main resin, including the following steps: S1.1: Take 30 parts by weight of fluorocarbon resin, add N,N-dimethylacetamide, stir evenly to prepare a dispersion with a fluorocarbon resin concentration of 50wt%, then add methacrylic acid resin and mix and stir at a speed of 200-300r / min for 5-10min; S1.2: Then add 3 parts by mass of glycidyl methacrylate and 30 parts by mass of dibasic acid ester DBE, and stir at a speed of 800-850 r / min for 3-3.5 hours; S1.3: After stirring evenly, 2 parts by weight of dispersant, 1 part by weight of epoxy resin defoamer and 1.5 parts by weight of leveling agent are added in sequence to obtain a weather-resistant main resin.

3. The method for manufacturing a weather-resistant crystalline silicon solar cell according to claim 2, characterized in that: Step S2: preparing a transparent coating liquid, comprising the following steps: S2.1: Add 100 parts by mass of weather-resistant main resin, 1.2 parts by mass of anti-hydrolysis agent, 2-3.9 parts by mass of nano-SiO2, 0.3 parts by mass of dispersant and 150 parts by mass of ethyl acetate into a beaker according to a certain amount, disperse at a speed of 1000-1200 r / min for 1-1.5 hours, and stand for defoaming for 20-25 minutes; S2.2: Then add 8.6-12.6 parts by mass of curing agent and 121-150 parts by mass of diluent, stir evenly, and obtain a transparent coating liquid.

4. The method for manufacturing a weather-resistant crystalline silicon solar cell according to claim 3, characterized in that: Step S6 assembling the solar cell includes the following steps: S6.1: Arrange the crystalline silicon cells and connect the positive and negative electrodes of the cells using solder strips or conductive paste to form cell strings and battery packs; S6.2: placing the arranged battery strings on the EVA film, covering with a glass panel and a weather-resistant transparent back sheet, and then placing in a laminator, curing under high temperature and high pressure to obtain a solar cell module; S6.3: Install an aluminum frame on the edge of the laminated battery assembly, install a junction box and connect the external circuit to obtain a weather-resistant crystalline silicon solar cell.

5. The method for manufacturing a weather-resistant crystalline silicon solar cell according to claim 4, characterized in that: The mass ratio of fluorocarbon resin to methacrylic resin is (9-5):

4.

6. The method for manufacturing a weather-resistant crystalline silicon solar cell according to claim 5, characterized in that: The anti-hydrolysis agent is a silane coupling agent, and the dispersant is a polysilicate dispersant.

7. The method for manufacturing a weather-resistant crystalline silicon solar cell according to claim 6, characterized in that: The curing agent is epoxy resin curing agent and the diluent is acetone.

8. The method for manufacturing a weather-resistant crystalline silicon solar cell according to claim 7, characterized in that: The mass ratio of acetone, 4-vinyl benzoate and 2,2,6,6-tetramethyl-4-hydroxypiperidine is 10:1:

3.

9. The method for manufacturing a weather-resistant crystalline silicon solar cell according to claim 8, characterized in that: The mass ratio of tetraethyl orthosilicate, deionized water, anhydrous ethanol, hydrochloric acid, hexadecyltrimethylammonium bromide and light stabilizer is 1:12:23:0.2:0.1:5.

Citation Information

Patent Citations

  • Fluoropolymer coated films useful for photovoltaic modules

    CN101351521A

  • Back sheet for solar cell module

    JP2013125780A

  • Backsheet for solar cell

    KR1020110030857A